2005
DOI: 10.1016/j.immuni.2005.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Marginal-Zone B Cell- Positive Selection in Spleen

Abstract: Antigen receptor-mediated signaling is critical for the development and survival of B cells. However, it has not been established whether B cell development requires a signal from self-ligand engagement at the immature stage, a process known as "positive selection." Here, using a monoclonal B cell receptor (BCR) mouse line, specific for the self-Thy-1/CD90 glycoprotein, we demonstrate that BCR crosslinking by low-dose self-antigen promotes survival of immature B cells in culture. In spleen, an increase in BCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
166
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(178 citation statements)
references
References 61 publications
12
166
0
Order By: Relevance
“…Similarly, it has been demonstrated Our finding of significantly increased anti-nucleosome IgM serum levels in E-Btk-2 Tg mice does not appear to reflect an increase in natural antibodies due to higher numbers of B-1 cells. This might be a possibility, as natural autoreactive B-1 B cells are positively selected by self-antigen [6,7]. But, in contrast to our E-Btk-2 mice, autoreactive B-1 cells are normally not efficiently driven into autoreactive IgM plasma cell formation: Tg mice that produce B cells specific for the Sm ribonucleoprotein, which is unique target in lupus, remain tolerant.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Similarly, it has been demonstrated Our finding of significantly increased anti-nucleosome IgM serum levels in E-Btk-2 Tg mice does not appear to reflect an increase in natural antibodies due to higher numbers of B-1 cells. This might be a possibility, as natural autoreactive B-1 B cells are positively selected by self-antigen [6,7]. But, in contrast to our E-Btk-2 mice, autoreactive B-1 cells are normally not efficiently driven into autoreactive IgM plasma cell formation: Tg mice that produce B cells specific for the Sm ribonucleoprotein, which is unique target in lupus, remain tolerant.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, it has been demonstrated that a natural serum autoantibody specific for the Thy-1 glycoprotein was produced in mice by B-1 cells that are positively selected by self-antigen [6]. Whereas lack of Thy-1 engagement in Thy-1 À/À mice permitted B cells specific for the Thy-1 glycoprotein to proceed to the follicular B-cell subset [32], increases in BCR signaling strength, induced by low-dose self-antigen, directed naive immature B cells to mature instead into the marginalzone B-cell subset [7]. It is therefore conceivable that LMP2A or Thy-1 antigen-mediated signals direct differentiation into B-cell subsets, whereas isolated Btk-mediated signals primarily affect cellular survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies suggest that the intact BCR-NF-jB signaling pathway is required for maintenance and responsiveness of mature MZ B cell pool. During the preparation of this manuscript, a study by Wen et al [58] demonstrated that low-dose antigen signaling is required for the positive selection of MZ B cells in the spleen. This study further supports our conclusion that CARMA1 may be involved in constitutive BCR signaling required for the maturation of different splenic B cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that BCR signal strength plays an important role in deciding B cell fate. B cells expressing a typical B1 BCR can be directed to MZ differentiation when Ag dose is reduced (43). Likewise, mutations that impair BCR signaling prevent B1 and FO but favor MZ B cell development, and mutations that enhance BCR signaling are associated with increased FO and decreased MZ B cells (26,76).…”
Section: The Cellular Origin Of Naamentioning
confidence: 99%